Further Tests of the Link between Unionization, Unemployment, and Employment: Findings from Canadian National and Provincial Data - Sran, Garry; Stanford, Jim (Just Labour: A Canadian Journal of Work and Society, 2009)
...[O]pponents of proposed changes to U.S. labour law (and, in particular, the Employee Free Choice Act) have attempted to argue that Canada’s labour market experience “proves” that unionization and collective bargaining produce higher unemployment and lower employment. One consultant’s study (Layne-Farrar 2009) has been especially important in making this argument. ...This article conducts a detailed econometric re-examination of Layne-Farrar’s counter-intuitive and sensational findings. --From executive summary